SYAL PRINTING DENGAN METODE VISUALISASI LUMEN PRINT LIMBAH BUAH JERUK - Ramdhan, Febi Muhamad; Maftukha, Nina (Anggada : Jurnal Desain dan Seni, 2021)
A Shawl that used lument print citrus waste as a motif. Lument print is a kind of primitive photography without using a camera.The shawl was designed with composition such a symmetrical and asymmetrical, and the rotation techniques on the results of lumen print.